2021
DOI: 10.48550/arxiv.2109.01547
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Teacher Mental Health During the COVID-19 Pandemic: Informing Policies to Support Teacher Well-being and Effective Teaching Practices

Joseph M. Kush,
Elena Badillo-Goicoechea,
Rashelle J. Musci
et al.

Abstract: While there is an emergence of research investigating the educational impacts of the COVID-19 pandemic, empirical studies assessing teacher mental health throughout the pandemic have been scarce. Using a large national dataset, the current study first compared mental health outcomes during the pandemic between pK-12 teachers and professionals in other occupations. Further, we compared the prevalence of mental health outcomes between in-person and remote teachers (n = 131,154). Findings indicated teachers rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Beyond the support teachers receive, students also play a key role in teacher mental health as the current study found student mental health as a significant predictor. Though previous studies have not explored this aspect, other studies have found the relationships teachers build with their students play a significant role in teacher mental health (Kush et al, 2021;Rodriguez et al, 2022). This was especially true for teachers in an online environment (Minihan et al, 2022;Walter & Fox, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the support teachers receive, students also play a key role in teacher mental health as the current study found student mental health as a significant predictor. Though previous studies have not explored this aspect, other studies have found the relationships teachers build with their students play a significant role in teacher mental health (Kush et al, 2021;Rodriguez et al, 2022). This was especially true for teachers in an online environment (Minihan et al, 2022;Walter & Fox, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have explored teacher job satisfaction, burnout, morale, and well-being at the beginning of the pandemic (e.g., Kush et al, 2021;Rogowska & Meres, 2022) and during the first full year of teaching during COVID-19 (e.g., Hutchinson et al, 2022;Zamarro et al, 2022). As COVID-19 and its effects waned in 2022, teachers still faced increased expectations for supporting students, incorporating technology used during the pandemic, and being flexible with students and teachers for COVID-related absences (e.g., virtual learning and covering of other classes).…”
Section: Methodsmentioning
confidence: 99%
“…Between March 2020 and February 2022, 567,000 teachers had left the profession in the U.S. (Jotkoff, 2022) and approximately 43% of teachers who left teaching in 2020 cited COVID-19 as their primary reason (Will et al, 2020). Compared to professionals from other professions (e.g., dentists, customer service representatives) teachers have reported greater mental health concerns, particularly among teachers who were forced to teach online, which was the majority of teachers (Kush et al, 2021). Though the quality of children's education has been greatly discussed in both academia and in the news, there has been relatively less attention to how teachers were faring in terms of mental health, job satisfaction, and receiving adequate support throughout the pandemic.…”
Section: Covid-19 and K-12 Teachers: Associations Between Mental Heal...mentioning
confidence: 97%
“…Since the early onset of the COVID-19 pandemic, public school teachers in the U.S. have been faced to navigate uncharted learning environments (e.g., online learning, hybrid models, and managing in-person), experienced tremendous strains to mental health, and reported dissatisfaction with the profession altogether (Baker et al, 2021;Chan et al, 2021;Herman et al, 2021;Kush et al, 2021;Marshall et al, 2023;Robinson et al, 2022;Will et al, 2020). Since March 2020, teacher attrition has become an increasingly major issue in the U.S.…”
Section: Covid-19 and K-12 Teachers: Associations Between Mental Heal...mentioning
confidence: 99%